Edukasi Pencegahan Low Back Pain pada Pekerja Bengkel dan Vulkanisir Ban Di Kabupaten Kutai Barat - Sari Oktaviani, Dea; Yulianti, Atika (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
Low Back Pain (LBP) is one of the most common musculoskeletal disorders experienced by workers engaged in physically demanding activities, such as those in automotive repair and tire retreading workshops. This condition is primarily caused by non-ergonomic postures, excessive lifting, and a lack of awareness of proper back stretching techniques. This community service program aimed to enhance workers’ knowledge and awareness of LBP prevention through physiotherapy education and simple exercise training. The activity was conducted at Sinar Ihsan Workshop and Tire Retreading in Kutai Barat Regency over three days in March 2025, involving 22 participants. The methods included educational counseling using leaflets, interactive discussions, and practical demonstrations of the William Flexion Exercise. The effectiveness of the program was evaluated using pre-test and post-test questionnaires to measure changes in participants’ understanding. Results showed a significant improvement in knowledge across all components from an average of 18.75% before the session to 100% after the training. Participants demonstrated enhanced understanding of the definition, causes, ergonomic work posture, and preventive exercise techniques for LBP. The program effectively increased workers’ awareness of the importance of maintaining correct posture and performing regular stretching exercises to prevent musculoskeletal injuries. This initiative highlights the role of physiotherapy-based education as an effective preventive approach for occupational health promotion. It is recommended that similar ergonomics and preventive physiotherapy training be continuously implemented among informal workers to minimize injury risks associated with repetitive physical activities.